Health Education in Improving Clean and Healthy Life Behavior (PHBS) at Community in the Jebol Ngrombo Village Baki Sukoharjo - Dewi Marfuah; Retno Dewi Noviyanti; Dewi Pertiwi Dyah Kusudaryati; Gharyn Utha Rahmala (Peneliti Teknologi Teknik Indonesia, 2022)
Based on the situation analysis obtained from the Nutrition Program Planning of the ITS PKU Muhammadiyah Surakarta Undergraduate Nutrition Program Students in 2021 in Jebol village RT 02 RW 01 Ngrombo Village, Baki District, Sukoharjo Regency, there is a problem that is still low awareness of clean and healthy living behavior (PHBS). In increasing awareness of the clean and healthy living behavior (PHBS) of the community in the broken village, it is necessary to carry out activities through counseling. The location of this service activity is in Jebol Village, RT 02 RW 01, Ngrombo Village, Baki District, Sukoharjo Regency. The target of this service activity is 23 PKK women. The stages of this service activity include preparing service locations and coordination, preparing anthropometric tools, preparing leaflets and power point materials about PHBS and hand washing properly, preparing pretest and posttest questions, measuring nutritional status, PHBS counseling and correct hand washing counseling. The result of this service is that most of the PKK mothers belong to the class I obesity category of 11 people (47.8%) and there is an increase in PHBS knowledge and hand washing in PKK mothers after being given nutrition education of 1.7 scores. Based on this, the conclusion that can be drawn is that participants in community service activities understand that clean and healthy living behavior and proper hand washing are very important to prevent various diseases.